ROLE OF GENERATION Z’S DECISION-MAKING IN ONLINE LOANS AND EASE OF USE AS A MODERATOR AMONG UNIVERSITY STUDENTS - Zakaria, Fakhmi; Alfaturachman, Ifnu Setya; Aprilya, Dandy; Salim, Salsa Filiya; Hidayah, Aulia Nurul (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2025)
Fintech Lending statistics report from OJK in 2023 that total online loans in Indonesia exceeded IDR 47 trillion as of June 2023, with Generation Z (aged 19–34) as the largest user group. This study analyzes the factors influencing Generation Z’s decision to use online loans, with ease of use as a moderating variable. A quantitative approach was applied using the Partial Least Squares (PLS) method through Smart-PLS 3.0. Data were collected through an online survey with 870 respondents. The findings indicate that financial literacy, lifestyle changes, consumerism, and trust significantly influence online loan decisions. However, ease of use only moderates the relationship between consumerism and online loan decisions, while its impact on other factors is insignificant. These results suggest that ease of use does not fully strengthen the relationship between these factors and online loan decisions. Further research is needed to explore its moderating role in this context..